Sutureless partial nephrectomy - S. V. Shkodkin; Yu. B. Idashkin; M. Z. A. A. Zubaidi; A. D. Kravets; A. F. Khuseinzoda; Zh. K. Askari; E. G. Ponomarev; V. Y. Nechiporenko; K. S. Shkodkin (Вестник урологии)
Introduction. A century and a half of experience in renal surgery has shown the clinical feasibility of preserving a functioning renal parenchyma and the pathogenetic validity of nephron-sparing surgery (NSS) in renal cell carcinoma (RCC).Objective. To analyze the available scientific publications on nephron-sparing sutureless kidney surgery or without  so-called renorrhaphy.Materials and methods. We have searched the eLibrary, PubMed, Сochrane Library and Scopus databases without time limits. A total of 19365 publications were found in the databases, including 71 randomized controlled clinical trials, 987 reviews of which 168 were systematic and 2 were performed based on data from the Cochrane Library. This review includes publications on the sutureless NSS technique in patients with RCC; clinical cases and abstracts were excluded from the formal analysis of publications. Thus, 132 publications were selected for the analysis, which are presented in the following independently or included in previous literature reviews. The studies available for analysis were quite heterogeneous in terms of patient groups, inclusion criteria, and control points, which did not allow for a meta-analysis of the data presented.Results. An attempt to abandon the principle of kidney suturing after partial nephrectomy was implemented using methods of hemostasis based on the action of physical factors. At the same time, the value of any one of the methods that seemed at first glance did not show obvious unequivocal advantages in the NSS, the achievement of which would unequivocally reduce the severity of the problematic issue at the present stage. Significant prerequisites for such a state of the problem should be considered the monocentric nature of most studies and relatively little experience in the application of certain methods or their combinations. In the aspect of the foregoing, it is difficult to disagree with the statement that many different methods of hemostasis used during NSS appear not only to be the result of the tireless search for new opportunities by clinicians, but also the real lack of universal technologies.Conclusion. An analysis of the advantages and disadvantages of the final hemostasis methods during NSS in patients with localized RCC indicates that this problem has not been solved and requires further research.